The Impact of Digitalization on Social Mobility in Contemporary Ukrainian Society - Holovach, N. A.; Chervona, S. P. (Statistics of Ukraine, 2025)
The purpose of the study was to statistically study the impact of digitalization on social mobility in modern Ukrainian society. The work uses such methods as analysis, synthesis, induction, deduction and generalization. The relevance of the research is determined by the significant impact of digitalization on social mobility in modern Ukrainian society. Due to global changes brought about by technological advances, digital tools are taking on an ever-increasing role in education, the economy, and social relationships. However, along with new opportunities, digitalization also creates significant challenges, including digital inequality, the risks of marginalization of social groups, and the loss of traditional mechanisms of social mobility. The problem is that unequal access to digital technologies, limited internet connectivity in rural and remote areas, as well as insufficient levels of digital literacy in certain social groups, create additional barriers to social and professional growth. The main factors affecting social mobility in the era of digital technologies are considered in the framework of the study. The problems that arise in the process of digitalization for various social groups, such as youth, older generations and residents of rural areas, are considered separately. It also highlights the importance of implementing digital literacy programs for different age groups, especially for older people who may not have sufficient experience in using digital technologies. The conclusions emphasize that in order to ensure social mobility in conditions of digitalization, it is important not only to stimulate the development of new technologies, but also to ensure access to them for all social groups, so that everyone has equal opportunities for self-realization and professional growth.